The Role of Teachers in Optimizing the Habit of Honesty in Children Aged 4-5 Years - Hani Febriani; Yulianti Fitriani; Roby Naufal Arzaqi (Universitas PGRI Madiun, 2026)
Moral development is interrelated with a person's self-control, which is also related to social rules. Honesty is a spiritual element, noble morals, and behavior that is in accordance with reality and truth. The purpose of this study is to determine the role of teachers in cultivating honesty in children and whether this role is running optimally. A qualitative approach with a case study method is the methodology of this study. The subjects were a class A teacher and a child. Data collection was carried out through observation, interviews, and documentation, then analyzed by reducing, presenting data, and drawing conclusions. The results of the study indicate that there are 4 roles of teachers as well as inhibiting and supporting factors in cultivating honesty in children in kindergarten, namely: 1) Teachers as educators understand the characteristics of children first and then cultivate honesty. Teachers as role models exemplify honesty to children during classroom activities. As teachers, they have their respective duties, but still cultivate honesty in children and do not emphasize materialistic values. However, in each activity, teachers insert honesty habits. Teachers become consultants for parents in their children's moral development and become mediators for children to solve and share their problems. 2) Inhibiting factors experienced by teachers are internal factors of children who are still closed and the environment around the child. 3) The supporting factors are family and school. The results of this study are recommended for teachers, schools, and future researchers as a reference strategy for shaping children's morals.